ABA-Dependent Salt Stress Tolerance Attenuates Botrytis Immunity in Arabidopsis - Haller, Eva; Iven, Tim; Feussner, Ivo; Stahl, Mark; Fröhlich, Katja; Löffelhardt, Birgit; Gust, Andrea A.; Nürnberger, Thorsten (Frontiers in Plant Science, 2020)
Plants have evolved adaptive measures to cope with abiotic and biotic challenges simultaneously. Combinatorial stress responses require environmental signal integration and response prioritization to balance stress adaptation and growth. We have investigated the impact of salt, an important environmental factor in arid regions, on the Arabidopsis innate immune response. Activation of a classical salt stress response resulted in increased susceptibility to infection with hemibiotrophic Pseudomonas syringae or necrotrophic Alternaria brassicicola and Botrytis cinerea, respectively. Surprisingly, pattern-triggered immunity (PTI)-associated responses were largely unaffected upon salt pre-treatment. However, we further observed a strong increase in phytohormone levels. Particularly, abscisic acid (ABA) levels were already elevated before pathogen infection, and application of exogenous ABA substituted for salt-watering in increasing Arabidopsis susceptibility towards B. cinerea infection. We propose a regulatory role of ABA in attenuating Botrytis immunity in this plant under salt stress conditions.